In vitro and in vivo evaluation of the effects of condensed tannins and catechins monomers on antioxidant and intestinal health of Chinese seabass (Lateolabrax maculatus) - Dong, Ruiqi; Qiu, Jianqiang; Cao, Junming; Huang, Wen; Chen, Bing; Zhao, Hongxia; Sun, Wenhao; Lu, Huijie; Loh, Jiun-Yan; Peng, Kai (Frontiers in Veterinary Science, 2025)
Plant-derived condensed tannins (CT) exhibit strong bioactivity of antioxidant, immunostimulation and intestinal protection, but with little clues of the mechanism of action. Since CT are consist of catechins (CAs) monomers, e.g., catechin (CA), epicatechin (EC) and epigallocatechin (EG), we motivated to use the monomers to explore the underlying mechanisms in a seabass model focusing on anti-oxidative stress and intestinal health of Lateolabrax maculatus. An in vitro intestinal primary cell oxidative stress model induced by hydrogen peroxide was set up to assess the antioxidant and immune activities of CT and CAs. Another 56–d feeding trial with 800 fish was conducted to evaluate the effects of CT and CAs on growth performance, intestinal permeability and digestive enzyme activities, intestinal morphology and antioxidant status, and intestinal bacterial flora of fish. Five diets were prepared to contain 0 (G1) and 1 g/kg of CT, CA, EC and EG. Fish were randomly distributed into 20 tanks with 4 tanks per diet and 40 fish per tank, and were fed to apparent satiation twice daily. Results showed that CT and CAs exhibited similar effects in alleviating hydrogen peroxide-induced cell injury by activating nuclear factor erythroid 2-related factor 2 gene expression, and improving antioxidant and immune capacities. Dietary CT and CAs enhanced intestinal antioxidant ability and increased (p < 0.05) the abundance of intestinal Firmicutes, Proteobacteria and Bacteroidetes to oxidative stress tolerant. With a dose of 1 g/kg CT and CA promoted (p < 0.05) intestinal total antioxidant capacity, but slightly induced intestinal injury mainly due to increased (p < 0.05) intestinal permeability (as reflected by increased lipopolysaccharide concentrations) and inhibited (p < 0.05) digestion (as reflected by the decreased trypsin and lipase activities) of fish. In summary, CT and CAs protect intestine from oxidative stress and improve intestinal antioxidant capacity by stimulating antioxidant enzyme system and bacterial flora. CA and EC show similar or superior antioxidant activity than CT.